Choice of Law in Latin American Arbitration: Some Empirical Evidence and Reflections on the Latin American Market for Contracts - Cuniberti, Gilles (2020)
The aim of this Article is to assess the preferences of parties to Latin American international business transactions when they choose the law governing their contracts. For that purpose, the authors have conducted an empirical analysis of data that they were able to gather from arbitral institutions active in Latin America, with a focus on years 2011 and 2012. Furthermore they offer some reflections on the results and elaborate on whether they can be explained by the territorial approach of choice of law in Latin America, the importance of the United States as a trading partner for Latin American countries and the extent to which Anglo-American lawyers are present on Latin American markets.